Human TDP1, APE1 and TREX1 repair 3′-DNA–peptide/protein cross-links arising from abasic sites in vitro. Issue 7 (29th March 2022) - Wei, Xiaoying; Wang, Zhishuo; Hinson, Caroline; Yang, Kun
Abstract: Histones and many other proteins react with abundant endogenous DNA lesions, apurinic/apyrimidinic (abasic, AP) sites and/or 3′-phospho-α, β-unsaturated aldehyde (3′-PUA), to form unstable but long-lived Schiff base DNA–protein cross-links at 3′-DNA termini (3′-PUA–protein DPCs). Poly (ADP-ribose) polymerase 1 (PARP1) cross-links to the AP site in a similar manner but the Schiff base is reduced by PARP1's intrinsic redox capacity, yielding a stable 3′-PUA–PARP1 DPC. Eradicating these DPCs is critical for maintaining the genome integrity because 3′-hydroxyl is required for DNA synthesis and ligation. But how they are repaired is not well understood. Herein, we chemically synthesized 3′-PUA-aminooxylysine-peptide adducts that closely resemble the proteolytic 3′-PUA–protein DPCs, and found that they can be repaired by human tyrosyl-DNA phosphodiesterase 1 (TDP1), AP endonuclease 1 (APE1) and three-prime repair exonuclease 1 (TREX1). We characterized these novel repair pathways by measuring the kinetic constants and determining the effect of cross-linked peptide length, flanking DNA structure, and the opposite nucleobase. We further found that these nucleases can directly repair 3′-PUA–histone DPCs, but not 3′-PUA–PARP1 DPCs unless proteolysis occurs initially. Collectively, we demonstrated that in vitro 3′-PUA–protein DPCs can be repaired by TDP1, APE1, and TREX1 following proteolysis, but the proteolysis is not absolutely required for smaller DPCs.